A Conservative and Compact Finite Difference Scheme for the Sixth-Order Boussinesq Equation with Surface Tension - Xiaofeng Wang; Weizhong Dai; Anjan Biswas (Mathematical and Computational Applications)
In this study, we propose a conservative and compact finite difference scheme designed to preserve both the mass change rate and energy for solving the sixth-order Boussinesq equation with surface tension. Theoretical analysis confirms that the proposed scheme achieves second-order accuracy in temporal discretization and fourth-order accuracy in spatial discretization. The solvability, convergence, and stability of the difference scheme are rigorously established through the application of the discrete energy method. Additionally, a series of numerical experiments are conducted to illustrate the effectiveness and reliability of the conservative scheme for long-time simulations.